Ellipsoid representation of reference templates for efficient speaker verification. - Kah-Chye Tan (IEEE Transactions on speech and audio processing)
In this correspondence, we propose a compact ellipsoid representation of the reference templates associated with a speaker. The representation captures crucial information about not only the speaker's characteristics, but also the intraspeaker variations. We also derive a from-ellipsoid-surface (FES) distance for use with the ellipsoid representation